Loss of Unconventional Myosin VI Affects cAMP/PKA Signaling in Hindlimb Skeletal Muscle in an Age-Dependent Manner - Lehka, Lilya; Wojton, Dominika; Topolewska, Małgorzata; Chumak, Vira; Majewski, Łukasz; Rędowicz, Maria Jolanta (Frontiers in Physiology, 2022)
Myosin VI (MVI) is a unique unconventional myosin ubiquitously expressed in metazoans. Its diverse cellular functions are mediated by interactions with a number of binding partners present in multi-protein complexes. MVI is proposed to play important roles in muscle function and myogenesis. Previously, we showed that MVI is present in striated muscles and myogenic cells, and MVI interacts with A-kinase anchoring protein 9 (AKAP9), a scaffold for PKA and its regulatory proteins. Since PKA directly phosphorylates the MVI cargo binding domain, we hypothesized that the cellular effects of MVI are mediated by the cAMP/PKA signaling pathway, known to play important roles in skeletal muscle metabolism and myogenesis. To elucidate the potential role of MVI in PKA signaling in hindlimb muscle function, we used mice lacking MVI (Snell’s waltzer, SV), considered as natural MVI knockouts, and heterozygous littermates. We used muscles isolated from newborn (P0) as well as 3- and 12-month-old adult mice. We observed a significant increase in the muscle to body mass ratio, which was most evident for the soleus muscle, as well as changes in fiber size, indicating alterations in muscle metabolism. These observations were accompanied by age-dependent changes in the activity of PKA and cAMP/PKA-dependent transcriptional factor (CREB). Additionally, the levels of adenylate cyclase isoforms and phosphodiesterase (PDE4) were age-dependent. Also, cAMP levels were decreased in the muscle of P0 mice. Together, these observations indicate that lack of MVI impairs PKA signaling and results in the observed alterations in the SV muscle metabolism, in particular in newborn mice.